PENGARUH INTENSITAS TEBANG BAYANG TERHADAP KELEMBABAN DAN DAYA DUKUNG JALAN HUTAN - Dulsalam Dulsalam; Apul Sianturi (Jurnal Penelitian Hasil Hutan, 1985)
Road maintenance has  been generally  considered  as a  major  cost  component in  logging cost.  An  investigation on the  effect of  shade  felling  intensity  on  the  moisture  content  and  bearing  capacity of  forest road was carried  out at the PT  Wisma Lukita  forest  concession  area,  located  in South  Sumatera.  Shade  felling  at the  right and left  side of forest roads is considered to be a  factor  which  affects  roads quality.  It is said to affect soil moisture  in the forest road structure, which in  turn  affects its  bearing capacity.In this study, the  effect  of a set of five shade felling intencity levels were investigated,  starting at 21 percent up to 70 percent  with 10 percent increments. The  effect on  moisture  content turns out  to be significant, and set of  five felling intensity  levels caused  moisture  contents to vary from 8 percent  to 20 percent. The effect on bearing capacity  however, is non-significant.